Rol de enfermería en el control de la tuberculosis pulmonar desde la perspectiva de la bioseguridad. Abril-agosto 2018. - Melendrez Pasmay, María Silvana (2018)
The objective of this bibliographical revision is to describe the role of nursing in the control of pulmonary tuberculosis from the perspective of biosecurity; a bibliographic and documentary-type study was carried out in which three criteria for the selection of information that are relevant, exhaustive and topical were applied, the inclusion criteria for this review were articles published in English and Spanish corresponding to the last five years; the results of this bibliographical research highlight the role that the nursing professional plays in the areas of management, research, teaching, direct attention to the patient, family and community, in addition to applying biosafety measures, have as purpose to reduce the spread of pulmonary tuberculosis to accomplish with the goals of the tuberculosis control programme and the objectives of sustainable development.